COMPARATIVE ANALYSIS OF MODERN COMPONENTS OF INFORMATION TECHNOLOGY FOR SOUND PROCESSING ON ROBOTIC SYSTEMS - Коротенко, Григорій; Фрідман, Костянтин (SWorldJournal, 2026)
The paper examines the current state and possibilities of processing information flows in modern robotic systems with artificial intelligence tools. Comparative characteristics of components of various systems and technologies are presented to assess the